(untitled) (gjstudies, 2016)
This research investigates the transformative impact of emerging computationaltechnologies on the requisite skill sets for accounting professionals, proposing a novelframework that diverges from traditional incremental adaptation models. While priorliterature has examined technology’s role in accounting, this study uniquely appliesprinciples from complex adaptive systems and cognitive science to model skill evolution as a non-linear, emergent phenomenon. We introduce the concept of ’technologicalsymbiosis thresholds’—critical points where human skills must fundamentally reconfigure rather than merely adapt—and identify three such thresholds relevant to currentaccounting practice: algorithmic auditing, blockchain-based verification, and predictiveanalytics integration. Through a mixed-methods approach combining computationalsimulation of skill networks with qualitative analysis of professional discourse from1995-2004, we demonstrate that technology adoption triggers skill requirement changesthat follow power-law distributions rather than linear progressions. Our findings revealthat approximately 22